Biotopic confinement of alien and native species of different-legged crustaceans (Amphipoda, Crustacea) in the conditions of waterbodies of Belarus - Makaranka, Andrei I.; Vezhnavets, Vasil V. (Journal of the Belarusian State University. Ecology, 2019)
For the first time, for aboriginal and alien species of different-legged crustaceans, the values of their occurrence in the basins of the main rivers of Belarus were determined. The most inhabited by alien species is the Pripyat River Basin, the aboriginal species in the first place is the basin of the r. Pripyat, and then Zap. Dvina and Neman. It was determined that the most common of alien species is Dikerogammarus haemobaphes [Eichwald, 1841], and of the native species – Gammarus least – the Neman River. In r. Western Dvina on the territory of Belarus alien species were not found. The occurrence of varsoviensis [Jazdzewski, 1975]. Within Belarus, all alien species are confined to flowing waters, and native species are found as lentic, and they are found as lent sets, as well as those that are found in the same way that they are found in lectures, and they are found as lent sets. The main types of biotopes in which isopod crustaceans are found. The number of habitats inhabited by alien species of amphipods is more diverse than that of native species: representatives of the native fauna are noted only in 4, and alien species in 10 biotopes. The large eurytopic character of invasive species may be a prerequisite for the success of the colonization of new habitats. It was established that the biotopic confinement depends on the age structure of the population in a specific habitat. The greatest difference in the average body size of alien species is mainly observed between plant and solid-substrate biotopes. Regardless of the origin of species for juveniles, preferred habitats are overgrown with higher aquatic vegetation.